Menstrual cycle related depressive symptoms and their diurnal fluctuations – an ambulatory assessment study - Hannah Klusmann; Annette Brose; Lars Schulze; Sinha Engel; Sebastian Laufer; Elise Bücklein; Christine Knaevelsrud; Sarah Schumacher (BMC Women's Health)
Abstract Background Reproductive mood disorders indicate that within-person variation in depressive symptoms across the menstrual cycle can be related to ovarian hormone changes. Until now, such cycle-related symptom changes have been measured once daily, even though depression research indicates systematic diurnal changes in symptoms. Further, previous research often focused on aggregated depression scores. This study examined whether three daily assessments of depressive symptoms follow similar trajectories across the menstrual cycle and investigated within-person cyclical fluctuation of all individual symptoms and the aggregated score. Methods 77 naturally-cycling participants (35 with and 42 without depressive disorder) provided three daily ratings of depressive symptoms across one menstrual cycle to evaluate individual and summarized symptoms. Results Reliability estimates (w) of the three diurnal measurements ranged from 0.56 to 0.78. Cyclicity showed statistically significant interindividual differences for all symptoms, and individual symptoms differed significantly from each other in their magnitude of cyclicity. Limitations Only one menstrual cycle was assessed to reduce participant burden. Further, ovulation testing dates were based on self-reported cycle lengths, and only LH (luteinizing hormone) peaks were tested without subsequent progesterone rises. Conclusions The results highlight the need for a symptom-specific approach to assess individual variance in cyclicity of depressive symptoms. Reliability for one daily assessment can be improved by using the afternoon value, a sum score for depressiveness, or multiple items per symptom. Furthermore, this study emphasizes, that depressive symptoms can systematically change across the menstrual cycle, and it is, therefore, important to include it in depression research. Exploring female-specific risk factors of depression will enable the development of person-tailored treatments. Trial registration The study was preregistered at ClinicalTrials.gov (NCT04086316) with the first registration on 27/08/2019.